Canine lymphoma case control database - Ruple, Audrey A.; Morley, Paul, S. (Colorado State University. Libraries, 1989)
These data were collected by the Veterinary Medical Database and include demographic information about 67,712 dogs seen at veterinary teaching hospitals in North America between 1989 and 2011. 18,826 of these dogs were diagnosed with lymphoma (cases) and the control series were matched to case dogs by institution of admission, age, and year of admission in up to a 3:1 ratio.

Cases 1990-2009; controls 1989-2011.
Zip file includes: data and readme file.
Authors are from Purdue University. Department of Comparative Pathobiology and Colorado State University. Department of Clinical Sciences.
Department of Clinical Sciences
Keywords: canine; dog; lymphoma; veterinary teaching hospital; case-control